Providing care for older adults in the Emergency Department: expert clinical recommendations from the European Task Force on Geriatric Emergency Medicine - Lucke, J. A.; Mooijaart, S. P.; Heeren, P.; Singler, Katrin; Mcnamara, R.; Gilbert, T.; Nickel, C. H.; Castejon, S.; Mitchell, A.; Mezera,; Van Der Linden, Lorenz; Lim, S. E.; et al. (European Geriatric Medicine, 2021)
Purpose Despite the rapidly expanding knowledge in the field of Geriatric Emergency Medicine in Europe, widespread implementation of change is still lacking. Many opportunities in everyday clinical care are missed to improve care for this susceptible and growing patient group. The aim was to develop expert clinical recommendations on Geriatric Emergency Medicine to be disseminated across Europe.
CRIS-Team WoS Importer:2021-11-12